El oso panda - Leeson, Tom.; Leeson, Pat. (San Diego, Calif. : Blackbirch Press, 2002)
Describes the physical appearance, habits, hunting and mating behaviors, family life, and life cycle of giant pandas.
Includes bibliographical references (p. [24]) and index.
07-10.
2-5.
Keywords: Giant panda -- Juvenile literature